(untitled) (Research, Society and Development, 2021)
The maxillary sinuses are the largest of the paranasal sinuses. They consist of pneumatized bilateral cavities, lined by respiratory mucosa, identical to the nasal mucosa, consisting of pseudostratified epithelium, with hair cells and goblet cells, producing mucus. Radiographically, the maxillary sinus is seen as a radiolucent area, ovoid or rounded, with a well-defined contour, delimited by a continuous radiopaque line or with small interruptions and radiolucency similar to that of the orbit. When a change in the maxillary sinus is suspected, images of the sinus are usually found, the presence of septa, thickening of the mucosa, or polyps. Sinusitis is the main pathology of the maxillary sinus, being of multifactorial etiology, and may be due to anatomical, environmental factors or viral, bacterial, or fungal infections. The diagnosis of sinusitis is clinical, but it can be confirmed by imaging exams such as panoramic radiography or cone beam computed tomography (CBCT). Case Presentation: In this case of a 21-year-old patient treated by the FOB-USP Surgery team, due to the proximity of the third molar to the maxillary sinus, a cone-beam scan was performed in which bubbles were noted on the surface of the maxillary sinus content. The image is compatible with sinusitis however, the presence of bubbles is a very unusual image in this type of alteration of the maxillary sinus. Conclusions: CT images with fluid levels and bubbles on their surface, although uncommon in dental practice, are characteristic of acute sinusitis and the dentist must have this knowledge for the correct diagnosis of maxillary sinusitis.